Prevalence of and Associations With Distress and Professional Burnout Among Otolaryngologists: Part II, Attending Physicians. (May 2021) - Carlson, Matthew L.; Larson, David P.; O'Brien, Erin K.; Lohse, Christine M.; Kircher, Matthew L.; Gurgel, Richard K.; Hunter, Jacob B.; Micco, Alan G.; Nogan, Stephen J.; O'Connell, Brendan P.; Rangarajan, Sanjeet V.; Rivas, Alejandro; et al.
Objective: To ascertain the prevalence of and associations with distress and professional burnout among academic otolaryngology attending physicians. Study Design: Cross-sectional survey. Setting: Twelve US academic otolaryngology programs. Methods: A questionnaire was administered that encompassed sociodemographic and professional features, the Expanded Physician Well-being Index for distress, the 2-item Maslach Burnout Inventory for professional burnout, the Patient Health Questionnaire–2 screen for major depressive disorder, and the Generalized Anxiety Disorder–2 screen for generalized anxiety disorder. Results: The survey response rate was 56% and included 186 attending physicians. The average respondent age was 47 years; 72% were men; 93% were married or partnered; and 86% had children. Distress was present in 40%, professional burnout in 26%, positive depression screening in 8%, and positive anxiety screening in 11%. In a univariable setting, age, hours worked in a typical week, nights on call in a typical week, and years of practice were significantly associated with distress, although in a multivariable setting, only hours worked in a typical week remained significantly associated with a positive Expanded Physician Well-being Index screen (odds ratio for each 10-hour increase, 2.61; 95% CI, 1.73-3.93; P < .001). In a univariable setting, hours worked in a typical week was significantly associated with a positive Maslach Burnout Inventory screen. Conclusion: Distress or professional burnout occurs in more than a quarter of academic otolaryngology attending physicians, whereas the prevalence of depression or anxiety is approximately 10%. The number of hours worked per week had the strongest association with distress and burnout. These findings may be used to develop and implement programs to promote physician well-being and mitigate professional burnout.